Громадсько-політичне, культурне та конфесійне життя української діаспори в Росії (1990-ті роки) - Кушнір, М. (Народна творчість та етнологія, 2019)
Українці – друга за чисельністю етнічна меншина в Російській Федерації. Українська діаспора в Росії – найбільша українська діаспора у світі. У другій половині 1980-х років на хвилі горбачовських реформ почалося відродження українського національного життя. Перше українське культурне товариство «Славутич» виникло 1988 року в Москві. Протягом 1990-х років українські товариства з’явилися в багатьох інших містах Росії. На початку 2000-х років існувало понад 100 українських об’єднань. Найбільшими були Організація українців Росії та Федеральна національно-культурна автономія «Українці Росії», що об’єднували менші спілки на регіональному і місцевому рівнях. Діяльність української діаспори в РФ здійснювалася в трьох основних напрямах: культурному, конфесійному та громадсько-політичному. Найбільш динамічно розвивався культурний напрям. Російська влада прагнула зосередити діяльність української діаспори виключно в культурному руслі й уникнути її політизації. Розвитку української діаспори в РФ сприяла велика правова база на міжнародному та національному рівнях. Загалом політика України щодо діаспори в Росії не проводилася на належному рівні. Українське керівництво не змогло вибудувати системи взаємодії та підтримки співвітчизників. Українська діаспора зазнавала протидії з боку російської влади. Найбільшим досягненням було відкриття 1998 року Культурного центру України в Москві. Українські культурні і громадсько-політичні об’єднання, церковні громади не досягли великих успіхів, оскільки були малочисельними та ізольованими одне від одного. Їм не вдалося створити повноцінної інфраструктури для ведення культурно-просвітницької роботи – бібліотек, шкіл, церков, видавництв та періодичних видань. Позбавлені підтримки з боку України та РФ, вони розпадалися або були пасивними. Ukrainians are the second-largest ethnic minority in the Russian Federation. The Ukrainian diaspora in Russia is the largest Ukrainian diaspora in the world. In the second half of the 1980s, on the wave of Gorbachev’s reforms, the revival of Ukrainian national life began. The first Ukrainian cultural society «Slavutych» arose in 1988 in Moscow. During the 1990s, Ukrainian societies appeared in many other cities of Russia. In the early 2000s, there were more than 100 Ukrainian associations. The largest were the Organization of Ukrainians in Russia and the Federal national-cultural autonomy «Ukrainians of Russia», which united smaller associations at the regional and local levels. The activity of the Ukrainian diaspora in the Russian Federation was carried out in three main directions: cultural, confessional, and public-political. The most dynamically developed cultural direction. The Russian authorities sought to concentrate the activity of the Ukrainian diaspora exclusively in a cultural direction and avoid its politicization. The development of the Ukrainian diaspora in the Russian Federation was facilitated by a large legal base at the international and national levels. In general, the Ukrainian diaspora policy in Russia has not been conducted at the appropriate level. The Ukrainian government was unable to build a system of interaction and support for compatriots. The Ukrainian diaspora was subject to resistance from the Russian authorities. The greatest achievement was the Cultural Center of Ukraine, which opened in 1998 in Moscow. Ukrainian cultural and public-political associations and church communities did not achieve great success because they were small and isolated from each other. They failed to create a complete infrastructure for conducting cultural and educational work—libraries, schools, churches, publishing houses, and periodicals. In the lack of support from Ukraine and the RF, they disintegrated or were passive.